Elicitation of preferences of Dutch broiler and pig farmers to support decision making on animal welfare. (1st March 2016) - Gocsik, Éva; van der Lans, Ivo A.; Lansink, Alfons G.J.M. Oude; Saatkamp, Helmut W.
Highlights: Dutch broiler and pig farmers preferred conventional practices to alternative practices. Farmers generally had negative preferences about free-range systems. Majority of farmers were not intrinsically motivated to convert to alternative systems. By mixing different methods the trustworthiness and quality of results can be enhanced. Abstract: Conjoint analysis was conducted to elicit Dutch broiler and fattening pig farmers' preferences about different characteristics of production systems, with primary interest in farmers' intrinsic motivation towards animal welfare (AW). A cluster analysis was carried out to identify distinct groups of farmers with homogeneous preferences. The results showed that farmers preferred conventional practices and had negative preferences towards free-range systems. Two clusters of broiler farmers were distinguished. The 'Free-range opposed' cluster evaluated a production system by focusing on a single aspect, the provision of free-range access, while the 'Multi-attribute focused' cluster included multiple attributes in their evaluation. In the case of fattening pig farmers, no clusters could be identified. Results showed that farmers do not have a strong intrinsic motivation to switch to a system with higher animal welfare standards. It is therefore likely that the level of on-farm AW will be determined by external and farm-specific factors, and that higher levels of AW will only be achieved if these factors are favorable for the adoption of these production systems.